Analysis of Slang Words in Song Lyrics Rap God By Eminem - I Made Verdy Natha; I Putu Mario Bintang Toti; Igo Bani Christian; Ni Nyoman Tri Sukarsih; Ni Made Diana Erfiani (International Journal of Linguistics and Discourse Analytics, 2022)
This study aims to determine the type of slang word used in a song lyric. The qualitative descriptive method is used in this study to collect and analyze the data from the song lyric. The source of the data was a song by Eminem entitled Rap God which was released in 2013. Theory of Allan & Burridge (2006) regarding type of slang words was used to analyze the data. From the analysis it was found that there are a total of 40 slang words in the song lyrics Rap God by Eminem. From those, there are five types of slang words used in the song lyrics namely Clipping, Blending, Fresh and Creative, Flippant, and Acronym. The most frequently used type of slang words is Clipping with a total of 26 data, while the least used is acronym with a total of only 1 data. The reason of why clipping type of slang words is frequently used is to match the flow or the genre of the song which is hip hop